Management of obstructed defecation - Podzemny, Vlasta (World J Gastroenterol, 2015)
The management of obstructed defecation syndrome (ODS) is mainly conservative and mainly consists of fiber diet, bulking laxatives, rectal irrigation or hydrocolontherapy, biofeedback, transanal electrostimulation, yoga and psychotherapy. According to our experience, nearly 20% of the patients need surgical treatment. If we consider ODS an “iceberg syndrome”, with “emerging rocks”, rectocele and rectal internal mucosal prolapse, that may benefit from surgery, at least two out of ten patients also has “underwater rocks” or occult disorders, such as anismus, rectal hyposensation and anxiety/depression, which mostly require conservative treatment. Rectal prolapse excision or obliterative suture, rectocele and/or enterocele repair, retrograde Malone’s enema and partial myotomy of the puborectalis muscle are effective in selected cases. Laparoscopic ventral sacral colporectopexy may be an effective surgical option. Stapled transanal rectal resection may lead to severe complications. The Transtar procedure seems to be safer, when dealing with recto-rectal intussusception. A multidisciplinary approach to ODS provides the best results.